Ethnopharmacology of The Tengger Tribe Society: Inventory Study of The Use of Medicinal Plants - Hadi Prayitno; . Ari P; Erwin Nur Rif’ah; Dewi Rokhmah (Journal of Global Pharma Technology, 2020)
The Tenggerese community is a community that inhabits the area commonly called "Tengger village". The community trust of the Tengger Tribe towards Mount Bromo and Mount Semeru is very large, so that it has created a close relationship between the people of Tengger Tribe and nature. The ethnobotany study is expected to not only be a documentation of traditional knowledge in the use of plants for subsequent generations, but also as one of the capital in the development and preservation of biological natural resources, especially for the use of traditional medicines in the Tengger tribe. This research is qualitative research. The results of the study indicate the occurrence of the Tengger Tribe Knowledge, Beliefs and Local Wisdom Inventory in Probolinggo Regency, with the decline in Tengger tribe knowledge and belief in the nature and benefits of medicinal plants. This was caused by the success of the health program by the government so that many residents took advantage of modern medicine when they were sick, Tengger Tribe who lived in Lumajang Regency showed the use of plants in every religious or cultural ritual or treatment, based on the teachings of their ancestors which is often done in the community around the informants from generation to generation. The Tengger tribe who lives in Pasuruan Regency shows that the rituals have been carried out from generation to generation and there are no special rituals when using the medicinal plants. The perceptions, attitudes and behavior of the community regarding the Tengger tribe medicinal plants in Probolinggo Regency showed a mediocre attitude because they had rarely used it as well as other forms of behavior, namely informants had not used the medicinal plants anymore, except for a few the older ones in the remote Tengger Mountain.In Lumajang, the type of traditional medicine in the Tengger tribe is actually still perceived and responded to quite positively by informants doing treatment in the traditional way within certain limits. However, they are more open to the patterns of modern medicine, especially among the younger generation. in Pasuruan Regency, residents perceive medicinal plants as plants that can treat a disease that they know from their ancestors before. Inventory of medicinal plants in the Tengger tribe domiciled in Probolinggo Regency there are at least 3 types of plants that are still used for medicinal purposes in the face of health problems such as red ferns, fennel and saffron plants. Whereas in Lumajang Regency uses include sugar cane plants, dlingu plants and banana plants for cases of health problems. The use of medicinal plants in Pasuruan Regency includes: dringu plants, black mustard greens, fennel, besides that there are also castor plants, muscle flour, ciplukan fruit, amethyst plants and ganjan plants. Keywords: Ethnopharmacology, Tengger Tribe, Society , Inventory Study, Medicinal Plants